A NEEDS ANALYSIS FOR KANJI LEARNING MEDIA FOR BEGINNERS - Nalurita; Setiana, Soni Mulyawan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Learning media using information technology is used to improve the quality of learning. This research aims to analyze students' needs regarding teaching materials for kanji learning media for beginners to make it easier for students to understand kanji. Therefore, the author will analyze the needs of students in learning kanji at the beginner level. The method used in this research is a qualitative descriptive method. Data collection was carried out by observation and distributing questionnaires to respondents. The results of the research show that there are still obstacles faced by students, namely that apart from source books, supporting media in learning kanji have not been used optimally. Therefore, the use of multimedia to increase student motivation and achievement is needed